2015
DOI: 10.1158/1078-0432.ccr-15-1046
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Exon 18 Mutations in Lung Cancer: Molecular Predictors of Augmented Sensitivity to Afatinib or Neratinib as Compared with First- or Third-Generation TKIs

Yoshihisa Kobayashi,
Yosuke Togashi,
Yasushi Yatabe
et al.

Abstract: Purpose: Lung cancers harboring common EGFR mutations respond to EGFR tyrosine kinase inhibitors (TKI), whereas exon 20 insertions (Ins20) are resistant to them. However, little is known about mutations in exon 18.Experimental Design: Mutational status of lung cancers between 2001 and 2015 was reviewed. Three representative mutations in exon 18, G719A, E709K, and exon 18 deletion (Del18: delE709_T710insD) were retrovirally introduced into Ba/F3 and NIH/3T3 cells. The 90% inhibitory concentrations (IC 90 s) of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
164
2
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(191 citation statements)
references
References 35 publications
20
164
2
5
Order By: Relevance
“…Then, we had a total of 134 G719X patients, of which 47 patients responded to 1st generation EGFR-TKIs (Table I). The average RR is 35.1% (47/134), indicating that G719X is a mutation of intermediate sensitivity, which is in accordance with previous reviews (16,4446) (Table II). …”
Section: Current Studies Of the G719x Mutation In Egfr In Nsclcsupporting
confidence: 92%
See 3 more Smart Citations
“…Then, we had a total of 134 G719X patients, of which 47 patients responded to 1st generation EGFR-TKIs (Table I). The average RR is 35.1% (47/134), indicating that G719X is a mutation of intermediate sensitivity, which is in accordance with previous reviews (16,4446) (Table II). …”
Section: Current Studies Of the G719x Mutation In Egfr In Nsclcsupporting
confidence: 92%
“…In addition, Yang et al reviewed patients with the G719X mutation who were treated with afatinib in the LUX-LUNG trial series and found that the overall response rate was 77.8% (14/18) (78). In laboratory studies, the G719A mutation exhibited higher sensitivity than Del19 in terms of both kinase activity and cell viability (16). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…for EGFR exon 18 mutations (20). Indeed, the ORRs to afatinib 40 mg/day seem to be higher than 55% for tumors harboring EGFR-G719X, L861Q or S768I mutations (17).…”
mentioning
confidence: 96%